Evaluation of palladacycles as a non-rhodium based alternative for the asymmetric conjugate 1,4-addition of arylboronic acids to α,β-unsaturated enones - Wong, Jonathan (2014)
The asymmetric conjugate 1,4-addition of arylboronic acids to α,β-unsaturated carbonyl compounds is an extremely versatile and widely used organic transformation. While the rhodium(I)-catalysed reaction has been thoroughly explored, the asymmetric palladium-catalysed protocol is far less developed and understood, particularly with acyclic enones as substrates. Herein, we report the systematic evaluation of a series of metallacycles for this reaction and the conjugate addition of arylboronic acids to a wide range of α,β-unsaturated enones, catalysed by an easily accessible and robust chiral phosphapalladacycle in high yields and enantioselectivities.